STEALING OR STEELING THE IMAGE? THE FAILED BRANDING OF THE GUERRILLERO HEROICO IMAGE OF CHE GUEVARA - Cambre, Maria-Carolina (Imaginations: Journal of Cross-Cultural Image Studies, 2012)
This article traces the ongoing tension between those who would characterize Alberto Korda’s famous image of Che Guevara, The Guerrillero Heroico, as a brand, trademark or logo, and those who insist it is a political/cultural icon and non-commercial and that these categories are mutually exclusive. The question of whether the image has been emptied of political content, and the debate around the copyrighting of an image considered by many to be in the public domain and a cultural icon are explored. The long-lasting struggle over the meanings and collective memories associated with this image indicate the possibility that both processes of commodification and radicalization of the image of Che Guevara can coexist. Using the literature on consumer research to engage definitions of branding as a commercially geared venture, this article teases out the problematics of different uses of the photograph and its derivatives, and highlights ambiguities around the notions of creation and authorship. After examining this image’s role within Cuba, Cuban use outside of Cuba, and its commercial and non-commercial uses by non-Cubans, I conclude that attempts at branding products with this particular image fail, and therefore its copyrighting is irrelevant.